Lending Rate Spread Shock and Monetary Policy Arrangements: A Small Open Economy Model for ASEAN Countries1. Issue 1 (March 2014) - Yoshimi, Taiyo
<x xml:space="preserve">Abstract</x> We investigate the welfare implications of monetary policy arrangements in a small open economy, considering firms' bank‐based finances that are widely observed in emerging ASEAN countries. The impact of an unexpected change in the lending rate spread, or a lending rate spread shock, depends on the presence of banking activity in the economy. This presence is important in Malaysia and Vietnam, where welfare effects of this type of shock are at least comparable to those of foreign monetary policy shocks. We also find that a rigid exchange rate arrangement amplifies the effect of a shock.